Role of adenosine A2A receptors in the neuroprotective effect of corticotrophin releasing hormone (CRH) - Valadas, Jorge Miguel de Sousa (2010)
Tese de mestrado, Bioquímica (Bioquímica Médica), Universidade de Lisboa, Faculdade de Ciências, 2010